Hubungan Supervisi Akademik Terhadap Disiplin Kinerja Guru - Aprionita, Rizti (Journal of Innovation in Teaching and Instructional Media, 2025)
This research aims to explore and analyze the relationship between academic supervision and teacher performance discipline at SD Negeri 26 Palembang. A quantitative approach using survey methods was employed in this research, where data was collected through questionnaires distributed to 16 teachers at SD Negeri 26 Palembang. The questionnaire measures teachers' perceptions regarding the process of academic supervision and their performance discipline, which includes aspects of attendance, adherence to rules, as well as responsibility in teaching and involvement in school activities. Data analysis was conducted using Pearson correlation technique to assess the strength and direction of the relationship between the variables. The research results show that there is a positive and significant relationship between academic supervision and teacher performance discipline. Planned and consistently implemented academic supervision contributes to the improvement of teacher discipline, especially in terms of punctuality, fulfillment of teaching responsibilities, and active participation in school activities. Teachers who receive regular supervision and constructive feedback tend to show higher levels of discipline compared to teachers who do not receive similar support. The implications of this research indicate that academic supervision not only serves as a monitoring tool but also as a development mechanism to enhance the quality of teachers' performance. Therefore, careful planning and effective implementation of academic supervision are crucial to encourage the improvement of teachers' performance discipline, which ultimately has a positive impact on the teaching and learning process and outcomes in schools.